Environmental software systems : computer science for environmental protection : 12th IFIP WG 5.11 International Symposium, ISESS 2017, Zadar, Croatia, May 10-12, 2017, Proceedings /: computer science for environmental protection : 12th IFIP WG 5.11 International Symposium, ISESS 2017, Zadar, Croatia, May 10-12, 2017, Proceedings. (2017) - Unknown
No abstract available